1991
DOI: 10.2527/1991.693985x
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters for live animal ultrasound, actual carcass data, and growth traits in beef cattle.

Abstract: Growth and carcass measurements were made on 2,411 Hereford steers slaughtered at a constant weight from a designed reference sire program involving 137 sires. A second data set consisted of ultrasound measures of backfat (USFAT) and longissimus muscle area (USREA) from 3,482 yearling Hereford cattle representing 441 sires. Restricted maximum likelihood procedures were used to estimate genetic parameters among carcass traits and live animal weight traits from these two separate data sets. Heritability estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
51
3
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 0 publications
16
51
3
3
Order By: Relevance
“…For TEMP, the scan traits were both phenotypically and genetically positively correlated with LWT. Arnold et al (1991), Robinson et al (1993), and Moser et al (1998) have reported similar results. No genetic estimates for scanned fatness traits were obtained for TROP due to failed convergence because little phenotypic variation existed for these traits at POSTW (e.g.…”
Section: Post-weaningsupporting
confidence: 72%
“…For TEMP, the scan traits were both phenotypically and genetically positively correlated with LWT. Arnold et al (1991), Robinson et al (1993), and Moser et al (1998) have reported similar results. No genetic estimates for scanned fatness traits were obtained for TROP due to failed convergence because little phenotypic variation existed for these traits at POSTW (e.g.…”
Section: Post-weaningsupporting
confidence: 72%
“…Fat cover was measured on yearling animals here, whereas it was a carcass trait in the review (Koots et al 1994b). Comparable ultrasonic measurements by Arnold et al (1991), Johnson et al (1993), Shepard et al (1996), and Moser et al (1998) revealed thin backfat with low estimated phenotypic variance (0.7 to 2.9 mm 2 ) as in our study. The coefficient of variation nevertheless was quite large (38%, in this report, based on the estimated phenotypic variance).…”
Section: Resultsmentioning
confidence: 57%
“…However, Meyer et al (1993), Meyer (1994), and Robinson (1996), using animal models, also reported consistently higher correlations than means from the review by Koots et al (1994b), which were based on estimates from various methods of analysis. Few literature estimates exist for the genetic correlation between weight and backfat, where both traits pertain to yearlings: -0.53 (Johnson et al 1993), -0.08 and 0.29 (Arnold et al 1991), 0.11 (Moser et al 1998), 0.16 (Banks et al 1996, and 0.45 (Turner et al 1990); the value from this study was well within the range, only marginally differed from zero (P < 0.10), and its absolute magnitude was reflected in the phenotypic estimate, but with opposite sign. Phenotypic correlations between weights were larger than literature means published by Koots et al (1994b) (0.36 and 0.72 between birth and weaning weight and weaning and yearling weight, respectively), like the direct genetic correlations but not to as great an extent.…”
Section: Correlations Between Traitsmentioning
confidence: 99%
“…Diversos autores observaram valores superiores aos do presente estudo para as médias de AOL e inferiores para EGS (Turner et al, 1990;Arnold et al, 1991;Moser et al, 1998;Kemp et al, 2002) efeito mais pronunciado observado através do processo de engorda. Ainda segundo o mesmo autor, a taxa de acúmulo de gordura nos machos inteiros é menor do que nos novilhos, que por sua vez é menor do que nas novilhas.…”
Section: Resultsunclassified